Novel instrument for inspecting rock bolt integrity using ultrasonic guided waves. (June 2021) - Stepinski, Tadeusz
Abstract: Design of an advanced instrument for inspecting rock bolt integrity by means of ultrasonic guided waves is presented. Issues related to features of multimodal and dispersive ultrasonic guided waves used by the instrument are addressed. Application of chirp compression technique in the form of broadband chirp signals capable of exciting long range guided waves is proposed and successfully verified using a new, portable instrument for rock bolt inspection. Performance of the instrument is illustrated by means of signals collected from real rock bolts. Highlights: Efficient ultrasonic non-destructive technique of rock bolts presented. Application of guided waves for rock bolt inspection implemented. Chirp pulse compression substantially improves SNR. Time–frequency processing for dispersion effects analysis. Performance of a portable rock bolt testing instrument demonstrated.